2004
DOI: 10.1007/s10096-004-1201-x
|View full text |Cite
|
Sign up to set email alerts
|

A case of cellulitis complicating Campylobacter jejuni subspecies jejuni bacteremia and review of the literature

Abstract: Infection with Campylobacter species is a predominant cause of food-borne gastroenteritis in the industrialized world. Bacteremia is detected in <1% of patients with diarrhea, mainly in immunocompromised hosts or those in the extremes of age. Reported here is the case of a 78-year-old, immunocompromised male patient with Campylobacter jejuni subsp. jejuni bacteremia complicated by cellulitis. The infection was characterized by a protracted course with several recurrences and refractoriness to multiple antibiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 21 publications
2
17
1
3
Order By: Relevance
“…Thus, the most appropriate protocols for antimicrobial treatment for bacteremic infections, whether caused by susceptible or resistant strains, have not been established. Successful outcomes have been reported previously, especially with the carbapenems (4,15,16,18). In previous studies, this antimicrobial group has also shown excellent in vitro activities against Campylobacter spp.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Thus, the most appropriate protocols for antimicrobial treatment for bacteremic infections, whether caused by susceptible or resistant strains, have not been established. Successful outcomes have been reported previously, especially with the carbapenems (4,15,16,18). In previous studies, this antimicrobial group has also shown excellent in vitro activities against Campylobacter spp.…”
Section: Discussionmentioning
confidence: 82%
“…Since extraintestinal manifestations are uncommon in campylobacteriosis, data on their antimicrobial therapy are based only on anecdotal case reports (4,18,21) and small retrospective case series (15,16). Thus, the most appropriate protocols for antimicrobial treatment for bacteremic infections, whether caused by susceptible or resistant strains, have not been established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such complications have also been reported in patients hospitalized with Campylobacter-related bacteremia and underlying health problems such as Campylobacterrelated meningitis [80,81], hepatitis [82], arthritis [83], abdominal septic aortic pseudoaneurysm [84], peritonitis [85,86], acute pancreatitis [87,88], cellulitis [89,90], pericarditis [91], endocarditis [92] and hemolytic uremic syndrome (HUS) [93]. Again, these reports indicate that Campylobacter is able to efficiently travel through the blood stream in gastroenteritis patients, specifically to tissues or organs that can only be reached via the circulating blood stream.…”
Section: Timing Of Detection In Hospitalsmentioning
confidence: 90%
“…5 Pacanowski ve arkadaşları, 2 5 yıllık süre zarfında 23 hastanenin katılımıyla yaptıkları çalış-mada, Campylobacter bakteriyemisi olan 178 hastanın 94'ünde (%53) C.fetus izole etmişler ve çoğu hastanın erkek ve yaşlı olduklarını bildirmektedirler. Aynı çalışmada hastaların %39'unda karaciğer hastalığı, %38'inde kanser olduğunu öte yandan…”
Section: öZetunclassified